Multi-index nonlinear robust virtual synchronous generator control method for microgrid inverters - Guo Yanan (Nonlinear Engineering, 2025)
New energy is widely used in power systems due to its advantages of being green and sustainable. However, it requires microgrid inverters (Mis) to connect to the power grid, and a large number of connections will cause the system to lack damping and inertia, which are not conducive to the stability of the power grid. To improve the control performance of MIs, the study first constructs a nonlinear virtual synchronous generator (VSG) control method based on differential geometry theory, and then combines multi-index nonlinear robust control to design the control method. The research results indicate that the nonlinear VSG control method can achieve frequency oscillations from 51.24 to 50.01 Hz in grid connected environments, with small fluctuations in the response of active and reactive outputs, as well as output phase currents. In off grid environments, it can quickly reach steady-state values without significant overshoot. In contrast with the traditional second-order VSG control method, the multi-index nonlinear robust VSG control method can achieve stability within the range of (49.98–50.04 Hz) and (0.1–1.0 kW) in the event of a fault in the MI system. In a parameter perturbation environment, frequency, active power, and output phase current can all quickly and smoothly reach stable values without static errors. The above outcomes indicate that the raised control method can effectively alleviate the adverse effects of external disturbances and parameter disturbances on MIs.